The development of a soccer-specific training drill for elite-level players - Kelly, D. M.; Gregson, W.; Reilly, T.; Drust, B. (The Journal of Strength and Conditioning Research, 2013)
The use of sports-specific technical practices as a physical training stimulus has increased in recent years in soccer. Such approaches, although effective, can produce different levels of physiological strain in the individual players within the session, thereby limiting the usefulness of the training session for all players. The aim of this study was to develop a high-intensity soccer-specific training (SST) drill that was not only based on the demands of match-play but also would reduce the variability in the physiological response to training compared with other specific drills. To evaluate this approach to training, the SST drill was compared with a "traditional" aerobic interval training (AIT) protocol and a small-sided games (SSG) drill. Each training protocol was carried out across 4 × 4-minute exercise bouts, interspersed by 4 × 3 minutes of active recovery. Mean ± SD heart rates (HRs) for the 4-minute exercise bouts during SST (175 ± 5 b/min) and AIT (174 ± 6 b/min) were significantly higher than that observed during the SSG protocol (170 ± 6 b/min; p < 0.05). Heart rate during the SST drill showed less interparticipant variability (mean ± SD HR ranged from 169 ± 6 to 180 ± 5 b/min) when compared with those during AIT (157 ± 8 to 186 ± 8 b/min) and SSG (143 ± 10 to 179 ± 78 b/min) training conditions. Ratings of perceived exertion (SST, 6 ± 2; AIT, 7 ± 1; SSG, 5 ± 1) across the entire exercise period were similar between the 3 training conditions (p > 0.05). These results indicate that the SST stimulates a more uniform physiological response than other currently adopted specific endurance training protocols used in soccer. This would suggest that it provides a valid alternative to the current approaches used for the aerobic training of players.